Electronic Fiscal Devices (EFDs) An Empirical Study of their Impact on Taxpayer Compliance and Administrative Efficiency - Casey, Peter (IMF Working Papers; Working Paper ;, 2015)
Several administrations have adopted electronic fiscal devices (EFDs) in their quest to combat noncompliance, particularly as regards sales and the value-added tax (VAT) payable on sales. The introduction of EFDs typically requires considerable effort and has costs both for the administration and for the taxpayers that are affected by the requirements of the new rules. Despite their widespread use, and their considerable cost, EFDs can only be effective if they are a part of a comprehensive compliance improvement strategy that clearly identifies risks for the different segments of taxpayers and envisages measures to mitigate these risks. EFDs should not be construed as the 'silver bullet' for improving tax compliance: as with any other technological improvement the deployment of fiscal devices alone cannot achieve meaningful results, whether in terms of revenue gains or permanent compliance improvements.